(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Metabolic syndrome is a complex pathological condition characterized by a combination of obesity, insulin resistance, arterial hypertension, and dyslipidemia, which significantly affect the structure and function of internal organs, particularly the kidneys. Vascular alterations within the renal cortex play a crucial role in the progression of renal dysfunction associated with metabolic disturbances. The aim of this study was to investigate the morphological features of renal cortical blood vessels in experimental metabolic syndrome. An experimental study was conducted using laboratory animals with induced metabolic syndrome. Histological examination of renal tissue was performed to evaluate vascular structural changes within the cortical layer of the kidneys. The results demonstrated significant morphological alterations in renal cortical vessels, including vascular wall thickening, narrowing of the vascular lumen, endothelial damage, and perivascular edema. Microcirculatory disturbances and signs of sclerosis were also observed in some specimens. These changes were more pronounced in the experimental group compared to controls. In conclusion, experimental metabolic syndrome leads to substantial morphological remodeling of renal cortical blood vessels, contributing to impaired renal microcirculation and progression of renal pathology. Early detection of vascular alterations may be important for preventing chronic kidney damage associated with metabolic disorders